UPAYA MENINGKATKAN MINAT BELAJAR PEMBELAJARAN IPS MELALUI COOPERATIVE LEARNING TIPE STAD PADA SISWA KELAS IV SDN SUDIMARA 5 KECAMATAN CILEDUG - Azzahra, Salsabilla; Yustia Suntari; Waluyo Hadi (STKIP Subang, 2026)
This study aims to increase student interest in social studies through the application of the STAD (Student Teams Achievement Divisions) cooperative learning model to fourth-grade students at SDN Sudimara 5, Ciledug District. Initial observations indicated that the learning process was still conventional and teacher-centered, resulting in low student interest. This was demonstrated by a lack of student activity, enthusiasm, and involvement in learning. This study was a Classroom Action Research (CAR) conducted in two cycles, with stages including planning, implementation, observation, and reflection. The results showed an increase in student interest in each cycle. In cycle I, student interest reached 62%, but did not meet the established success indicators, so it was continued in cycle II. In cycle II, student interest increased to 86%, reaching the very high category. Based on the research results, it can be concluded that the application of the STAD cooperative learning model is effective in increasing student interest in social studies